2018
DOI: 10.1007/s10802-017-0381-7
|View full text |Cite
|
Sign up to set email alerts
|

In the Eye of the Beholder? Parent-Observer Discrepancies in Parenting and Child Disruptive Behavior Assessments

Abstract: This study examined parent-observer discrepancies in assessments of negative child behavior and negative parenting behavior to shed more light on correlates with these discrepancies. Specifically, we hypothesized that informant discrepancy between observers and parents on child behavior would be larger when parents reported high levels of negative parenting (and vice versa) because high levels of these behaviors might be indicators of negative perceiver bias or patterns of family dysfunctioning. Using restrict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 85 publications
3
43
1
1
Order By: Relevance
“…In childhood and pre-puberty, previous results on gender differences have been inconsistent [11,13,17]. Since parental reports were used for children, one possible explanation for the present results might lie in a parental tendency to rate sleep and behavioral difficulties worse in boys than girls [4,40]. Previous studies have suggested that boys are more likely to exhibit externalizing behavior, while girls are more likely to exhibit internalizing behavior [40,41].…”
Section: Sleep-related Difficulties In Children and Adolescentsmentioning
confidence: 55%
See 1 more Smart Citation
“…In childhood and pre-puberty, previous results on gender differences have been inconsistent [11,13,17]. Since parental reports were used for children, one possible explanation for the present results might lie in a parental tendency to rate sleep and behavioral difficulties worse in boys than girls [4,40]. Previous studies have suggested that boys are more likely to exhibit externalizing behavior, while girls are more likely to exhibit internalizing behavior [40,41].…”
Section: Sleep-related Difficulties In Children and Adolescentsmentioning
confidence: 55%
“…Since parental reports were used for children, one possible explanation for the present results might lie in a parental tendency to rate sleep and behavioral difficulties worse in boys than girls [4,40]. Previous studies have suggested that boys are more likely to exhibit externalizing behavior, while girls are more likely to exhibit internalizing behavior [40,41]. When the children cannot sleep at night, boys might be more likely to receive attention through acting-out behavior, while girls might be more compliant and, therefore, attract less attention [41].…”
Section: Sleep-related Difficulties In Children and Adolescentsmentioning
confidence: 93%
“…First, both conduct problems and maternal depressive symptoms were measured using parent report. While effects of parenting programs on observed child behavior tend to be of similar magnitude as effects on parent-reported child behavior (Menting et al, 2013), parent-reported and observed measures of child behavior correlate only modestly (Moens, Weeland, Van der Giessen, Chhangur, & Overbeek, 2018). In our case, using parent-reports of conduct problems seems both a strength and a limitation.…”
Section: Discussionmentioning
confidence: 97%
“…Adolescents' self-report of internalizing symptoms may be different (and more valid) than reports by their parents (Kuhn et al 2017). There is also some evidence to suggest that sociodemographic, economic, and family factors can also influence disagreement in symptom reporting between children and parents and between parents and teachers (Moens et al 2018). For example, living in a oneparent family has been associated with both teacher-parent disagreement and childparent disagreement (Van Roy et al 2010;Cheng et al 2018).…”
Section: The Role Of Informantsmentioning
confidence: 99%